Pemanfaatan Desain Poster Paket Trip Untuk Menunjang Pemasaran Jasa di PT. Pratama Wisata Lintasnusa (Yukbanyuwangi) - mia, sulaibatul aslamiyah; Fadlillah, Hidayatul; f, h (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2024)
Travel destination marketing is increasingly shifting towards visually engaging and persuasive, with package trip poster design being a key element in attracting target market attention. The dedication activity focuses on designing a trip package poster that can help to support curiosity. Activities range from market and target audience analysis, in-depth understanding of destinations, and application of engaging graphic design principles. In this activity involved the z and millennial genes, which are the main segment of today's travel market. The result is the basis for creating appropriate and relevant visual messages. The design process blends elements – creative elements like colors, typography, and engaging images, all of which are tailored to brand identity and marketing purposes. The use of photographic techniques and digital illustration adds an engaging artistic and aesthetic dimension. The result is a series of trip package posters that highlight the visual appeal of destinations that are usually marketed through social media platforms like Instagram, Facebook and printed posters distributed through specific events. This design makes a positive contribution to marketing efforts that enhance competitiveness in a competitive travel industry